2008
DOI: 10.1007/s10533-008-9182-y
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of recent soil carbon in the humid tropics following land use changes: evidence from aggregate fractionation and stable isotope analyses

Abstract: Quantitative knowledge of stabilizationand decomposition processes is necessary to understand, assess and predict effects of land use changes on storage and stability of soil organic carbon (soil C) in the tropics. Although it is well documented that different soil types have different soil C stocks, it is presently unknown how different soil types affect the stability of recently formed soil C. Here, we analyze the main controls of soil C storage in the top 0.1 m of soils developed on Tertiary sediments and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 48 publications
1
42
0
1
Order By: Relevance
“…In oxidic soils, especially Oxisols, microaggregation is stronger, which enables them to resist higher compaction pressures. Also, it has been recently shown that aggregation and organic C stabilization depend strongly on soil mineralogy (Paul et al, 2008). This is further supported by results of a field study where the C MIC of a sandy-loam soil was not altered by tractor traffic, possibly because the porous space was not reduced enough to affect the microbial population (Lee et al, 1996).…”
Section: Resultsmentioning
confidence: 64%
“…In oxidic soils, especially Oxisols, microaggregation is stronger, which enables them to resist higher compaction pressures. Also, it has been recently shown that aggregation and organic C stabilization depend strongly on soil mineralogy (Paul et al, 2008). This is further supported by results of a field study where the C MIC of a sandy-loam soil was not altered by tractor traffic, possibly because the porous space was not reduced enough to affect the microbial population (Lee et al, 1996).…”
Section: Resultsmentioning
confidence: 64%
“…In this study, a simple approach is presented to discern the effect of sewage sludge application on the short-term SOC pool across a wide range of agricultural soils. The role of soil properties in the C sequestration of recently added carbon was also studied since little is known about this contribution (Paul et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However the potential for carbon sequestration in the soil in these Eucalyptus plantations on savannah is thought to be limited because soil under native savannah is less carbon depleted than cropland soils and because sandy soils do not contain large amounts of carbon relative to finer textured soils (Six et al 2002;Stewart et al 2007Stewart et al , 2008. In any case, the change in soil carbon after afforestation is commonly more pronounced in coarser particle-size fractions (Feller and Beare 1997;Li et al 2005;d'Annunzio et al 2008), which means that recently incorporated soil C is less stabilized than carbon remaining from the native ecosystem (Paul et al 2008).…”
Section: Introductionmentioning
confidence: 99%